Quantifying Disconnection of Groundwater From Managed‐Ephemeral Surface Water During Drought and Conjunctive Agricultural Use. Issue 7 (22nd July 2019) - Fuchs, Erek H.; King, James Phillip; Carroll, Kenneth C.
Abstract: The physics of disconnection between interrelated surface and groundwater has evolved considerably in recent years, especially since conjunctive use of water resources is increasingly dependent on groundwater resilience, but methods to measure disconnection on a river basin scale are lacking especially for managed‐ephemeral and irrigated‐agricultural systems. Multiyear drought limited surface water along Rincon Valley within the Elephant Butte Irrigation District (EBID) in the arid, Lower Rio Grande Basin of south‐central New Mexico, USA, and effects were compounded by continued extraction of groundwater to meet crop requirements. Average year‐end water table elevations in recent years have been below the average elevation of the riverbed, indicating potential disconnection between the river and the aquifer even when the river flows during the irrigation season. This study analyzed data from EBID groundwater monitoring wells adjacent to the river, infiltration determined from river flows, and riverbed measurements along the Rincon Valley reach to determine net annual seepage discharge to the aquifer and annual average pressure head below the river. Annual assessment from 2010 to 2017 confirmed that the drought shifted the system from connection to transition and then to disconnection. Nonlinear regression was used to quantify this shift to disconnection and back, enabled determination of several disconnection process metrics, and was also used to confirm that nonlinear disconnection behavior was reversible without significant hysteresis. The method developed herein confirms that the total head difference transition threshold can be determined from river/riparian monitoring sites over reach to basin scales. Key Points: A field method was developed to quantify surface‐groundwater interaction shift from connection to transition, and from transition to disconnection The 2010 to 2017 drought was used to quantify shift to disconnection and back, which enabled determination of several disconnection process metrics Watershed‐scale nonlinear disconnection behavior was quantified, reversible, and without significant hysteresis